Chinese Military Modernization and the Open Door Policy - Rovit, Sam B. (Tufts Archival Research Center, 2005)
Volume 12, Issue 1. Winter When China began to open its doors to the West, party leaders gave top priority to economic development, deemphasizing the role of the military. Deng Xiaoping himself stated that the international situation made it possible for China to spend less on defense and more on economic construction. But the military has not been entirely neglected in the pursuit of these new policies. Sam Rovit focuses on what the Open Door has meant for the Chinese military - and concludes that its gains from Westernization have been substantial.